A model to determine payments associated with radiology procedures. (December 2017) - Mabotuwana, Thusitha; Hall, Christopher S.; Thomas, Shiby; Wald, Christoph
Highlights: Radiology departments currently receive operational reports only at an aggregate level, typically at a cost-center level. There is little visibility into how the transactional nature of the radiology business relates to the financial rewards. Having visibility into procedure level payments can contribute to economic success, especially in a capitated system. Charge-to-total charge ratio can be used to approximate radiology payments at a procedure level. Abstract: Objective: Across the United States, there is a growing number of patients in Accountable Care Organizations and under risk contracts with commercial insurance. This is due to proliferation of new value-based payment models and care delivery reform efforts. In this context, the business model of radiology within a hospital or health system context is shifting from a primary profit-center to a cost-center with a goal of cost savings. Radiology departments need to increasingly understand how the transactional nature of the business relates to financial rewards. The main challenge with current reporting systems is that the information is presented only at an aggregated level, and often not broken down further, for instance, by type of exam. As such, the primary objective of this research is to provide better visibility into payments associated with individual radiology procedures in order to better calibrate expense/capital structure of the imaging enterprise to the actual revenue or value-add to the organization it belongs to. Materials and methods: We propose a methodology that can be used to determine technical payments at a procedure level. We use a proportion based model to allocate payments to individual radiology procedures based on total charges (which also includes non-radiology related charges). Results: Using a production dataset containing 424, 250 radiology exams we calculated the overall average technical charge for Radiology to be 873.08 per procedure and the corresponding average payment to be 326.43 (range: 48.27 for XR and 2750.11 for PET/CT) resulting in an average payment percentage of 37.39% across all exams. Discussion: We describe how charges associated with a procedure can be used to approximate technical payments at a more granular level with a focus on Radiology. The methodology is generalizable to approximate payment for other services as well. Understanding payments associated with each procedure can be useful during strategic practice planning. Conclusions: Charge-to-total charge ratio can be used to approximate radiology payments at a procedure level.